Estrutura e florística de Samambaias e Licófitas em uma cronossequência de vegetação secundária e na floresta primária na Amazônia Oriental - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2016)
This study aims to evaluate the composition changes in the structure and species of fern and lycophyte communities from the eastern Amazon, in a chronosequence analysis. The floristic survey was conducted in a total of 40 areas (covering 10,600 km2) belonging to the Ecological Research of Long Duration of the Caxiuanã National Forest Project (PELD Caxiuanã). Thirty-seven areas now contain secondary vegetation that arose after historical use of such areas under “slash and burn” agriculture, and the age of such vegetation ranges from 1 to 45 years old. As a control, 3 areas of primary forest were also surveyed. The plots were selected based on information collected through interviews with the local community about the historic usage of the territories and the amount of time since abandonment. All areas were topographically located and had a similar plateau, and they were all near the primary forest. The areas were categorized into four age classes: Class 1 (secondary vegetation from 1-10 years old); Class 2 (11-25 years); Class 3 (26-45 years) and Class 4 (control areas - 100 years). In each area a plot of 20 x 20 m was selected from which floristic data were collected: terrestrial species were collected in the usual way, epiphytes and hemiepiphytes were collected in corticicolous substrate from tree species having DBH (diameter at breast height) ≥ 5 cm up to 2m tall. The soil variables (pH, organic matter, moisture, Al, Ca, Ca + Mg, K, Mg, Na and concentrations of fine sand, coarse sand, water dispersible clay, total clay and silt) and canopy cover were analyzed to identify the importance of this environment to the community´s structure. 1,769 individuals were sampled belonging to 20 species, of which 12 were epiphytes and 7 were terrestrial and Lomariopsis japurensis was the only hemiepiphyte recorded. The most abundant species were Selaginella parkeri (1364), Polytaenium guayanense (89), Hecistopteris pumila (71) and Trichomanes vittaria (58). The secondary vegetation showed the highest number of unique species (12 species), whereas the primary forest showed only three. There was no variation in the density of individuals in relation to age group (p = 0.823), but there was a relationship between density and species abundance (p = 0.005). The analyzed environmental variables are not correlated with species abundance and density of individuals in the analyzed community. The ordination analysis NMDS showed that there are changes in the floristic composition by age class, which is more related to soil variables: organic matter, pH, fine sand and silt. This study showed that regeneration in fern and lycophyte communities in areas of cutting and burning in the eastern Amazon is marked by a clear pattern of replacement species according to likely changes in microhabitat over time.
Keywords: Samambaias; Licófitas; Vegetação secundária; Morfologia; Cronossequência; Variáveis edáficas; Amazônia Oriental; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL